1991
DOI: 10.1007/bf02630988
|View full text |Cite
|
Sign up to set email alerts
|

Differential stabilization of cytochrome P-450 isoenzymes in primary cultures of adult rat liver parenchymal cells

Abstract: Cytochrome P-450 dependent hydroxylation of testosterone was measured in 7-day-old cultures of primary rat liver parenchymal cells. Determinations were carried out in monocultures of parenchymal cells and co-cultures of parenchymal cells with rat liver nonparenchymal epithelial cells, or mouse embryo fibroblasts. In the monoculture system, testosterone metabolism was drastically reduced and hardly measurable after 7 days in culture. In the co-culture systems, individual P-450 isoenzymes were stabilized on diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…These two features could be related because in pure hepatocyte cultures the addition of proteoglycans improves gap junction activity (137). The enhanced survival and function of hepatocytes cocultured with rat liver epithelial cells have been confirmed by many investigators (134,(138)(139)(140)(141)(142)(143); the induction of CYP2B1 and CYP2B2 by phenobarbital has also been demonstrated (137,144). Moreover, other cells have been effective, including both liver endothelial cells and nonhepatic cells (145)(146)(147).…”
Section: However Survival and Metabolic Compe-mentioning
confidence: 87%
“…These two features could be related because in pure hepatocyte cultures the addition of proteoglycans improves gap junction activity (137). The enhanced survival and function of hepatocytes cocultured with rat liver epithelial cells have been confirmed by many investigators (134,(138)(139)(140)(141)(142)(143); the induction of CYP2B1 and CYP2B2 by phenobarbital has also been demonstrated (137,144). Moreover, other cells have been effective, including both liver endothelial cells and nonhepatic cells (145)(146)(147).…”
Section: However Survival and Metabolic Compe-mentioning
confidence: 87%
“…NEC establishment and culture NEC were initiated as described before (16). In brief, thin liver slices from an adult, male Sprague-Dawley rat were repeatedly digested with trypsin.…”
Section: Chemicalsmentioning
confidence: 99%
“…why were GST activities increased and not those of UDPGT, or how the changes on the DNA level are linked to the changes in enzyme activities or cell size. Experience has shown (14,16) that single physiological parameters that are crucial for the differentiated status of a given cell type in vitro may be regulated independently and, thus, may respond differently to external factors. Furthermore, different types of cells react differently to agents such as sodium butyrate.…”
Section: Mw (Kda)mentioning
confidence: 99%
“…Indeed, a co-culture model of primary hepatocytes and rat liver epithelial cells has been developed in our laboratory ; this has been used in pharmaco-toxicological studies and remains one of the most effective and practical experimental approaches to obtain extended hepatocyte survival and functional activity. Although several reports have demonstrated expression of biotransformation activities in this system (BCguC et al, 1983(BCguC et al, , 1993Niemann et al, 1991;Perrot et al, 1991;Utesch et al, 1991;Donato et al, 1994), limited data are yet available with regard to CYP mRNA expression. Akrawi et al (1993) have shown that co-cultures maintained mRNAs encoding CYP2BlI 2, CYPlA2, NADPH: cytochrome P-450 reductase and cytochrome b,, together with a significant induction of CYP2B mRNA and protein following exposure to phenobarbital.…”
mentioning
confidence: 97%